IMPLEMENTASI KEBIJAKAN PERTAMBANGAN BATUBARA DI KOTA SAWAHLUNTO - Salmarita, Syafni; Yuliani, Febri (Saraq Opat: Jurnal Administrasi Publik, 2023)
The coal mining sector is a strategic sector in efforts to improve welfare, but coal mining activities can result in changes to the physical environment and have an impact on changes in social, cultural and economic life. The implementation of coal mining policies in the City of Sawahlunto where problems that arise are incompatibility with existing regulations and SOP with conditions in the field. The purpose of this study was to determine the implementation of coal mining policies in the City of Sawahlunto and the inhibiting factors for the implementation of coal mining policies in the City of Sawahlunto. The theoretical concept used in this research is the theory of public policy implementation by Donald Van Metter & Carl Van Horn. The method used in this research is descriptive qualitative. The results of this study indicate that the implementation of coal mining policies in the City of Sawahlunto has not run optimally due to constraints on the implementation of the policy on resource indicators, the characteristics of implementing agents and social, political and economic impacts. Factors that become obstacles in implementing the policy are environmental damage and pollution due to coal mining business/activities, there are individuals who do not comply with SOP, lack/limitation of local workforce in the coal mining sector.